Betaine alleviates obesity-related metabolic disorders in rats: insights from microbiomes, lipidomics, and transcriptomics - Xian Wang; Xin Shang; Yan Pan; Yu Fu; Huilian Zhu; Shuxun Yan (Frontiers in Nutrition)
BackgroundBetaine is a natural food component that plays an important role in improving body composition, but the details of its effects on adipose tissue remains to be elucidated. Here, we hypothesize that betaine can alleviate obesity-related metabolic disorders, thus gut microbiota, transcriptomics and lipidomics were used to investigate the obesity-alleviating effects of betaine on high-fat diet (HFD)-fed rats.MethodsIn this study, rats fed a HFD were subjected to an 8-week oral intervention with betaine. We measured changes in body weight (BW), blood lipid profiles, and gastrointestinal hormones to assess therapeutic effects. The epididymal white adipose tissue was extracted and stained to evaluate the pathological morphology of adipocytes. The structure of the rat gut microbiota and the expression profiles of lipid metabolism-related genes in adipocytes were analyzed using 16S rRNA sequencing and transcriptomics. Furthermore, the lipid metabolomics of adipose tissue samples was investigated using an LC-MS analysis platform.ResultsOur findings imply that betaine has been linked to the alleviation of community alterations in gut microbiota resulting from HFD, facilitating the proliferation of beneficial microbiota (e.g., Lactobacillu, Lachnospiraceae_NK4A136_group) and the generation of short-chain fatty acids (SCFA). Particularly, our results indicate that betaine treatment led to notable variations in the content of DHA-riched glycerophospholipids which exhibited a positive correlation with the secretion of intestinal hormone (e.g., cholecystokininand peptide YY). Additionally, betaine upregulated the expression of genes related to thermogenesis and glycerophospholipids metabolic pathways in the adipose tissues.ConclusionOur findings indicate that betaine has the potential to decrease HFD-related obesity by regulating adipose tissue metabolism and promote the synthesis of polyunsaturated phospholipid rich in DHA. The underlying mechanism of betaine action might encompass its influence on gut microbiota modulation and SCFA metabolism.